(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: FoMO is experienced by many adolescents who constantly update information. The majority of adolescents have accessed information through Instagram on their mobile phones. Thus, adolescents cannot separate from a mobile phone called nomophobia, which can affect social interaction as apathetic those around called phubbing behavior. This study aims to determine the relationship between FoMO and nomophobia with phubbing behavior among adolescent Instagram users. Methods: This cross-sectional study was conducted on 319 respondents in Depok who were selected through a purposive sampling technique based on inclusion and exclusion criteria. This study was conducted using valid and reliable questionnaires: the FoMO adaptation scale) (r=0.720), the Nomophobia Questionnaire (NMP-Q) (r=0.901), and the Phubbing Scale Questionnaire (r=0.920). Univariate analysis was performed for categorical data using the frequency distribution test and central tendency test for numerical data, while the bivariate test used Pearson Correlation. Results: The correlation analysis of FoMO with phubbing behavior showed moderate correlation strength and positive direction (p=0.001), (r=0.446), while the results of the correlation analysis of nomophobia with phubbing behavior showed weak correlation strength and positive direction (p=0.001), (r=0.395). Conclusion: FoMO and nomophobia have a relationship with phubbing behavior among adolescent Instagram users. Health promotion and early detection of FoMO, nomophobia, related to phubbing behavior is essential to prevent disruption of adolescent development. Further research regarding improving self-management skills when using mobile phones can be provided.